Transcriptomic profile of cumulus cells isolated from cumulus-oocyte complexes of prepubertal and adult sheep - Martino, Nicola Antonio; Temerario, Letizia; Parisi, Francesco; Mansi, Luigi; Bogliolo, Luisa; Mastrorocco, Antonella; Ariu, Federica; Podda, Andrea; Ciani, Elena; Manzari, Caterina; Picardi, Ernesto; Pesole, Graziano; et al. (Theriogenology, 2026)
Cumulus cells (CCs) are crucial during cumulus-oocyte complex (COC) growth, maturation and fertilization. Analysis of gene expression in CCs of in vitro matured oocytes help to identify non-invasive biomarkers of oocyte quality. This study compared transcriptomic profiles of CCs from matured oocytes of prepubertal (<6 months) and adult (3–5 years) sheep. COCs were individually in vitro cultured for in vitro maturation (IVM). After IVM, CCs were removed and only those isolated from matured oocytes were collected and analyzed. Samples (20–25 COCs/sample), 5 prepubertal vs 5 adults, were processed for RNA extraction, library preparation and deep transcriptome sequencing. Reads were aligned to the sheep reference genome (Oar_v3.1) using STAR (version 020201) and differentially expressed genes (DEGs) identified with DESeq2 (p < 0.05, |log2fc|>1.2). GO, KEGG, and gene network analyses elucidated gene functions, with validation via quantitative PCR. Results showed 1024 identified DEGs, 819 upregulated and 205 downregulated, in prepubertal sheep CCs. GO analysis associated with gene network enrichments allowed the identification of key genes of CC functionality related to donor age. In detail, DEGs were found to be involved in important CC functions such as: aromatase activity (CYP19A), growth factor-binding proteins (ERBB3, IGFBP2/3, PDGFRA, ITGAV), mitochondrial functions (SOD1, ATP5MF-ATP, ATPase H+/K+, MT-COX1/2/3, ND4L, NDUFS4, COX17) and regulation of cell-cell/cell-matrix interactions mediated by: integrins (ITGA6/L/V, ITGB4/8), collagen (COL1A/3A/5A) and cadherins (CDH4/6/13/17/18/23, DSG2). These findings enhance understanding of molecular mechanisms underlying oocyte development from early life to fertile age and offer potential non-invasive biomarkers of oocyte quality of adult cyclic subjects.